PELAKSANAAN METODE RESITASI PADA PESERTA DIDIK UNTUK MENINGKATKAN KARAKTER TANGGUNGJAWAB - Adya Pribadi, Reksa; Fuadi Dakwan, Ahmad; Mawardi, Fadel (STKIP Subang, 2021)
There are many ways that can be done by an educator in strengthening character such as through various forms of learning methods or techniques, one of which is giving assignments or commonly called the recitation method. The research which aims to find out whether the inculcation of the character of responsibility can still be done in distance learning and how the process of strengthening the character of responsibility of students through the recitation method is carried out by taking place at SDN Serang 21 for the academic year 2020-2021. The approach in this study is a qualitative approach. In collecting data, researchers used two data collection techniques, namely observational studies and interviews. Based on the scope of the synchronization between theory and what is happening in the field, especially at SDN Serang 21 which we used as the research location, it can be concluded that so far the effectiveness of the recitation method in strengthening the character of the responsibility of students is going quite well, this is illustrated by how students can collect assignments on time and try to complete tasks well.